Factors that Affected the Mortality Rate of Chronic Obstructive Pulmonary Disease Patients with Respiratory Failure - Nahrisyah, Putri; Syarani, Fajrinur; Tarigan, Amira P; Ashar, Taufik (Jurnal Respirologi Indonesia, 2025)
Background: Chronic obstructive pulmonary disease (COPD) is a significant health issue with high morbidity and mortality rates. However, risk factors for COPD, particularly in cases with type II respiratory failure, are not fully understood. This study analyzes factors influencing the mortality rate of COPD patients with type II respiratory failure. Methods: This observational study used a cross-sectional design, analyzing medical records of COPD patients with type II respiratory failure treated at H. Adam Malik General Hospital, Medan, from November 2021 to September 2022. A total of 42 patients met the inclusion criteria. Data analysis included descriptive statistics and inferential tests using the Chi-Square test and multiple logistic regression to identify the most dominant factors. Results: Among the 42 patients, the mortality rate was 50%. Variables such as gender, age, number of comorbidities, smoking habits, and history of exacerbations were not significantly associated with mortality. Patients who did not regularly use inhalers had a 19-fold higher mortality risk than those who did (P=0.004; OR=19.79; 95% CI=2.67-146.99). Length of stay was inversely associated with mortality, with each additional day reducing the risk by 0.77 times (P=0.011; OR=0.77; 95% CI=0.63-0.94). Conclusion: Routine inhaler use and length of stay are significant factors influencing the mortality rate in COPD patients with type II respiratory failure.